CORAK KAJIAN GENDER DALAM PERSPEKTIF NASR HAMID ABU ZAID - Khoirul Anwar (LP2M Universitas Ibrahimy, 2012)
Men andwomenwill always be differentboth biologically andsocially. In thebiologicaldimensionsof menandwomendifferin physical terms, the difference is adifferencekondratiformthat can not bealteredor formedby humans. The natureofthisbiologicaldimension ofpermanent anduniversal. This sidewillalways be the sameinanycountryorinany culturewhatsoever, there will be nodifferences of opinionabout the genderof menand womenwhenconcernedwith thebiological. NasrHamidAbuZaydis one of thecontroversialIslamicthinkerswhomuch gives his viewsin the Islamicstudies. This paperwill explorehis thoughts ongender